Bottom contact behaviour by humpback whales in Brazilian waters: first underwater observations at Trindade Island. Issue 1 (December 2016) - Pinheiro, Flavia; Pinheiro, Hudson; Siciliano, Salvatore; Santos, Robson
Abstract Few records of humpback whales (Megaptera novaeangliae ) have been made in Brazilian oceanic waters. This article reports the first record of bottom contact behaviour by humpback whales in Brazilian waters and adds four new sightings of the species to Trindade, an island located 1160 km from the Brazilian coast. The bottom contact behaviour has been associated with moult and hygienic functions for some cetaceans. The change of water temperature, triggered by the migration from cold Antarctic waters to the warm tropical Trindade coast, could have accelerated the turnover of skin superficial layers and the moulting process to this humpback whale here reported. Despite such uncertain reason of the behaviour, this novel record comes to increase the behavioural repertoire for the humpback whales in Brazilian waters, may be possibly an additional cleaning strategy.